Alice in Wonderland in Film and Popular Culture - Sanna, Antonio (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book examines the many reincarnations of Carroll's texts, illuminating how the meaning of the original books has been re-negotiated through adaptations, appropriations, and transmediality. The volume is an edited collection of eighteen essays and is divided into three sections that examine the re-interpretations of Alice in Wonderland and Through the Looking-Glass in literature, film, and other media (including the branches of commerce, music videos, videogames, and madness studies). This collection is an addition to the existing work on Alice in Wonderland and its sequels, adaptations, and appropriations, and helps readers to have a more comprehensive view of the extent to which the Alice story world is vast and always growing. Antonio Sanna (PhD, University of Westminster) teaches English in Sassari, Italy. He is the co-editor of the series Critical Companions to Contemporary Directors and has edited volumes on historical and fictional pirates, the last season of Twin Peaks and Welsh writer Arthur Machen.
1 'Introduction: Alice and the Critics,' Antonio Sanna -- Part I: Alice on the Page -- 2 'A History of the Literary and Graphic Adaptations and Appropriations of Alice,' Antonio Sanna -- 3 "How Does It Taste: Eating and Drinking with Alice at the International Table," Olga Bukhina -- 4 'Charles Lutwidge Dodgson in Wonderland: Lewis Carroll's Mythobiography and Contemporary Fiction,' Maciej Skowera -- 5 "Reflecting on Wonderland: Alice's Adventures as Metatext in the Graphic Novel," Brigid Cherry -- 6 'Mad World: Disillusionment and Perceived 'Madness' in Batwoman Elegy,' Eileen M. Harney -- 7 'We're All Mad Here: Alice Goes to Gotham,' Rick Hudson -- Part II: Film Adaptations -- 8 'Standing in Contrast: An Examination of Conflict and Contrast in Various Adaptations of Alice's Adventures in Wonderland,' Joy E. Morrow and Christopher Flavin -- 9 'Alice Gets Mathematical: Carroll, Disney, and Donald in Mathmagic Land,' Martin F. Norden -- 10 'Alice, Interrupted: Reflecting on the Changing Chronology of the Girl in Disney's Looking-Glass,' Alexandra Heatwole -- 11 'Through a Darker Looking Glass: Alice's Adventures in Horrorland,' Lindsey Scott -- 12 'Alice's Evolution: Chicago 70 and the Revolutionary Awakening of Lewis Carroll's Victorian Heroine,' Andrew Grossman -- 13 'Alice's Adventures in Wondercity. Who am I? Revelation of the Self and Class Consciousness in Woody Allen's Alice,' Carla Fusco -- Part III: Alice's Adventures in Other Media -- 14 '(In)Appropriate Alice: The Neo-Victorian Sexualization of Carroll's Wonderland,' Anne-Marie Beller and Claire O'Callaghan -- 15 'Alice in the City,' Joanna Madlock -- 16 'Transformations: Aimer's 'I Beg You' and Alice in Japanese Music Video,' Masafumi Monden -- 17 'Navigating the Coded Rabbit Hole: A Sociocultural Reading of the American McGee's Alice Games,' Dominique Angela Juntado and Antonio Sanna -- 18 'The Immortal Hatter, Eternally Present with Alice,' Amanda Rutherford and Sarah Baker -- 19 'As Above So Below? Madness and Nonsense in Alice's Adventures in Wonderland', Emily Scherzinger and Jeffery Donaldson.
Keywords: Motion pictures; Popular Culture; Adaptation (Literary, artistic, etc.).; Literature, Modern-19th century; Film Studies; Popular Culture; Adaptation Studies; Nineteenth-Century Literature